Desarrollo de neumoconiosis y trabajo bajo la modalidad de tercerización en trabajadores peruanos del sector minero - Cáceres-Mejía, Brenda (2016)
Objetives. The aim of this study is to evaluate the association between the time of outsourced work and the development of pneumoconiosis in Peruvian miners who attended the "Centro Nacional de Salud Ocupacional y Protección al Ambiente para la Salud" between 2008 and 2011. Materials and methods. Retrospective case-control study. Cases were defined as workers diagnosed of pneumoconiosis under standardized criteria. Outsourced work was defined as the time (in months) of work in a company that does not own the primary mining project. The project owner company was registered in the Mining Companies Directory (Ministerio de Energía y Minas). We used multiple logistic regression with crude and adjusted ORs. Results. The study comprised 391 cases and 1519 controls. In both groups, most of the study subjects had a level of education lower than complete high school and were born and currently lived in the Peruvian highlands. There was statistically significant association between more frequency of pneumoconiosis and working 10 or more years in an outsourced company (OR: 1.50; 95%CI: 1.05-1.14; p=0.026). Miners with pneumoconiosis were more likely not to have education (OR: 3.07; 95%CI: 1.55–6.08; p=0.001), be currently living at the Peruvian highlands (OR: 1.40; 95%CI: 1.10-1.78; p=0.007) and to have more than 20 years of underground work history (OR: 8.92; 95%CI: 4.53-18.25; p<0.001). Conclusions. A statistically significant association was found between pneumoconiosis and the time of outsourced work. Not having education, residing in the Peruvian highlands and the time of underground work were associated risk factors.